To complete squares we first need to leave the variables in one side of the equation:
![\begin{gathered} x^2-8x-1=0 \\ x^2-8x=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/t3p4rmb7r9evmqh1adazefnfdqvuy7tlzn.png)
Now we take the coefficient of the linear term, we divide it by two and squared the result. We add the result in borh sides of the equation:
![\begin{gathered} x^2-8x+(-(8)/(2))^2=1+(-(8)/(2))^2 \\ x^2-8x+(-4)^2=1+(-4)^2 \\ x^2-8x+16=1+16 \\ x^2-8x+16=17 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/plx8sz6zt4dntwd0rgfhxahx4o77tvh6rm.png)
the left side is now a complete squared:
![(x-4)^2=17](https://img.qammunity.org/2023/formulas/mathematics/college/idcigfhhx3axc8fbpvawa8o1tymhcgxm2w.png)
Therefore the number that we had to add in both sides of the equation is 16.